Los desafíos de la UE en materia migratoria: la cooperación con terceros estados - Abad Quintanal, Gracia (UNISCI Discussion Papers, 2007)
The European Union is confronted with two main challenges as far as migration issues are concerned: the difficulties to achieve a common approach on these issues and the impossibility to address them within the narrow limits of one of the EU pillars. As a response to the second of these challenges the EU has designed the so called “global approach”. The article analyses the EU cooperation with third states as well as its importance for the global approach and the difficulties entailed by such cooperation.